Implementasi Kebijakan Benchmark dalam Mendeteksi Tingkat Kemampuan Wajib Pajak Badan pada Perusahaan Manufaktur Sub Sektor Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2021 - Ratu Wilandari; Siti Hamidah Rustiana; Sulhendri Sulhendri (Departement of Mathematics Education, 2023)
This study aims to analyze whether or not there are significant differences in the ability of taxpayers with the Benchmark Policy from the Directorate General of Taxes. The data used in this study is secondary data in the form of company financial reports that have been published on the Indonesia Stock Exchange for the period 2017 to 2019. The population in this study was 26 companies in the Food and Beverage Industry Sub Sector. The method used in determining the sample is purposive sampling including companies listed on the Indonesia Stock Exchange (N=55 and T=5 years). This research uses hypothesis testing using paired sample t-test with panel data. The results of the model test show that: 1) The results of the analysis show that there is a significant difference between GPM WP Agency and GPM Benchmarking DGT for Manufacturing Companies in the Food and Beverage Industry Sub Sector listed on the Indonesia Stock Exchange, 2) The results of the analysis show that there is a significant difference between OPM WP Badan with OPM Benchmarking DGT for Manufacturing Companies in the Food and Beverage Industry Sub Sector listed on the Indonesia Stock Exchange, 3) The results of the analysis show that there is a significant difference between PPM WP Badan and PPM Benchmarking DGT for Manufacturing Companies in the Food and Beverage Industry Sub Sector listed on the Indonesia Stock Exchange, 4) The results of the analysis show that there is a significant difference between the CTTOR WP Agency and the CTTOR Benchmarking DGT in Manufacturing Companies in the Food and Beverage Industry Sub Sector listed on the Indonesia Stock Exchange